2018
DOI: 10.15252/emmm.201708046
|View full text |Cite
|
Sign up to set email alerts
|

miR‐29 contributes to normal endothelial function and can restore it in cardiometabolic disorders

Abstract: We investigated the role of microRNAs (miRNA) in endothelial dysfunction in the setting of cardiometabolic disorders represented by type 2 diabetes mellitus (T2DM). miR‐29 was dysregulated in resistance arterioles obtained by biopsy in T2DM patients. Intraluminal delivery of miR‐29a‐3p or miR‐29b‐3p mimics restored normal endothelium‐dependent vasodilation (EDVD) in T2DM arterioles that otherwise exhibited impaired EDVD. Intraluminal delivery of anti‐miR‐29b‐3p in arterioles from non‐DM human subjects or rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 57 publications
(83 reference statements)
2
67
2
Order By: Relevance
“…miR‐29a remarkably improves the endothelial function in human T2DM arterioles and facilitates the restoration of endothelium‐dependent vasodilation in resistance arterioles . miR‐29a negatively regulates the expression of myeloid cell leukaemia 1 (MCL‐1), a prosurvival protein indispensable for the survival and function of cardiomyocytes and VSMCs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐29a remarkably improves the endothelial function in human T2DM arterioles and facilitates the restoration of endothelium‐dependent vasodilation in resistance arterioles . miR‐29a negatively regulates the expression of myeloid cell leukaemia 1 (MCL‐1), a prosurvival protein indispensable for the survival and function of cardiomyocytes and VSMCs .…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are key regulators in the function of cardiomyocytes, endothelial cells (ECs), vascular smooth muscle cells (VSMCs) and platelets which involve in the initiation and progression of atherosclerosis—the main cause of CAD. miR‐29a is required for normal function of endothelial cells and can restore it in cardiometabolic disorders . miR‐29a also takes part in the survival and function maintenance of cardiomyocytes .…”
Section: Introductionmentioning
confidence: 99%
“…14 However, these findings contrast with studies that reported either higher circulating levels of miR-29 in subjects with prediabetes 37 and type 2 diabetes 35,37 or lower miR-29b levels in those with prediabetes 38 and who developed type 2 diabetes in the prospective population-based Bruneck study. 39 It is tempting to speculate whether miR-29b is up-regulated in type 2 diabetes as a failed attempt to compensate for the endothelial dysfunction, as 27 The authors showed that miR-29 is required for normal endothelial function and can restore it in cardiometabolic disorders. 27 In addition, evidence obtained in knockout mice revealed that the miR-29 family has a protective role in beta cells and a pathogenic function in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…39 It is tempting to speculate whether miR-29b is up-regulated in type 2 diabetes as a failed attempt to compensate for the endothelial dysfunction, as 27 The authors showed that miR-29 is required for normal endothelial function and can restore it in cardiometabolic disorders. 27 In addition, evidence obtained in knockout mice revealed that the miR-29 family has a protective role in beta cells and a pathogenic function in the liver. 40 Paradoxically, increased miR-29 expression was reported to lead to increased insulin resistance, and decreased insulin secretion and signaling in metabolic tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation